Evaluación de estrategias de control del Nemátodo (Meloydogine sp) en gypsophila (Gypsophila paniculata) variedad Over Time en la finca Santa Martha Cayambe –Ecuador 2011 - Ramírez Quezada, Johanna Maricela (2012)
Ecuador is a productive country, rich in flora and fauna. A variety of products are exported worldwide, including the flower sector occupies an important place as it is within the leading exporters of flowers. The nematode presence and is an important factor for causing physical damage to the crop both for economic loss represented by low performance, nematodes that infect plants produce symptoms in both roots and foliage. Symptoms on roots are galls or knots on her injuries, excessive branching root, root rots when accompanied by fungi or bacteria. The existence of certain types of plant parasitic nematodes that feed on the juices flowing by the roots of plants is a serious problem for any farm with a soil with a high population of nematodes, as their attack can determine the future survival of the entire crop.